The Effect of Purgative Manna on the Infant Jaundice: Jaundice treatment by purgative manna - Azadbakht, Mohammad; Pishva, Narges; Mohammadi Samani, Soliman; Alinejad, Fatema (Iranian Journal of Pharmaceutical Sciences, 2005)
Infant jaundice is observed during the first week of life in approximately 60% of term and 80% of preterm infants. Hyperbilirubinemia may lead to the development of kernicterus, hearing loss, and convulsion. The goal of therapy in hyperbilirubinemia is lowering blood bilirubin levels or at least preventing its increase. It is recommended that phototherapy and if unsuccessful, blood exchange transfusion be used to keep bilirubin in the normal levels. In the Iranian traditional medicine, Cotoneaster manna (purgative manna) is commonly used in the treatment of infant jaundice. However, no scientific data was available regarding its effectiveness. In this study, purgative manna which was obtained from Cotoneaster discolor Pojark from south eastern Iran was used as an oral drop preparation. After standardization of the manna and the drop, clinical study was performed on 200 hyperbilirubinemic newborns. The serum bilirubin was assayed twice a day, using spectrophotometric method. The results showed that 88% of the infants who were treated by purgative manna plus phototherapy were cured during the first 3 days of administration, but only 21% of the infants who were treatment by phototherapy alone were cured.